A Comprehensive Risk Control Analysis of Shorebase Loading and Unloading Processes Using HIRARC, HAZOP, and Delphi Methodologies - Dian Aulia Hidayati Chardiwan; Luh Putri Adnyani; Muhammad Khaisar Wirawan (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Shorebase loading and unloading operations in the offshore oil and gas supply chain involve intensive interactions among heavy equipment, workers, dock conditions, and hazardous materials. Although standard safety procedures are commonly implemented, previous assessments have often applied HIRARC, HAZOP, or expert judgment separately, leaving a methodological gap in how field-based hazards, process deviations, and expert validation can be integrated into a single risk-control framework. This study addresses that gap by combining Hazard Identification, Risk Assessment, and Risk Control (HIRARC), Hazard and Operability Study (HAZOP), and the Delphi method to analyze loading and unloading risks at PT. X, East Kalimantan. HIRARC identified 14 work-activity hazards, of which 57.14% were categorized as moderate risk and 42.86% as insignificant risk. HAZOP identified 14 operational deviations, consisting of 71% low-risk and 29% moderate-risk deviations. Expert validation through two Delphi iterations confirmed key risk priorities related to working at heights, hazardous-material handling, heavy-equipment operation, night work, and adverse weather. The integrated approach demonstrates that HIRARC is effective for capturing direct field hazards, HAZOP strengthens deviation-based process analysis, and Delphi reduces subjectivity by validating mitigation priorities through expert consensus. The results provide practical recommendations for improving shorebase safety governance through routine inspections, competency-based training, lighting improvement, traffic control, early warning systems, and stricter supervision.